2022
DOI: 10.1177/02692163221097309
|View full text |Cite
|
Sign up to set email alerts
|

Medical communication and decision-making about assisted hydration in the last days of life: A qualitative study of doctors experienced with end of life care

Abstract: Background: The impact of assisted hydration on symptoms and survival at the end of life is unclear. Little is known about optimal strategies for communicating and decision-making about this ethically complex topic. Hydration near end of life is known to be an important topic for family members, but conversations about assisted hydration occur infrequently despite guidance suggesting these should occur with all dying people. Aim: To explore the views and experiences of doctors experienced in end-of-life care r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…In fact, clinical scales often include eating and drinking as sentinel acts that signal EOL (e.g., the Palliative Performance Scale [ 8 ]), and disinterest in eating and drinking can be confounded as a sign of depression or apathy. Instead, HCPs monitor clinical signs and work with residents and families to make complex decisions about nutrition at EOL [ 9 ]. With a high prevalence of dementia in LTC and a high proportion of LTC residents rated as cognitively impaired [ 10 ], capacity can be limited, and decision-making about nutrition care falls to substitute decision-makers (often family members), which can be very stressful [ 3 , 6 , 7 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, clinical scales often include eating and drinking as sentinel acts that signal EOL (e.g., the Palliative Performance Scale [ 8 ]), and disinterest in eating and drinking can be confounded as a sign of depression or apathy. Instead, HCPs monitor clinical signs and work with residents and families to make complex decisions about nutrition at EOL [ 9 ]. With a high prevalence of dementia in LTC and a high proportion of LTC residents rated as cognitively impaired [ 10 ], capacity can be limited, and decision-making about nutrition care falls to substitute decision-makers (often family members), which can be very stressful [ 3 , 6 , 7 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of the clinical management of EOL, decisions about artificial nutrition create more ethical dilemmas than other treatments, including artificial hydration and antibiotic therapy [ 17 ]. Yet, discussion about nutrition and hydration decisions is often not germane to care, and evidence suggests that HCPs do not consistently involve residents and families in these important healthcare decisions [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…13 Broader literature has considered professionals' communication with patients and family members about declining oral intake 14 and clinically assisted hydration. [15][16][17][18] The latter provides some evidence that attitudes towards clinically assisted hydration are rooted in cultural and religious beliefs. [16][17][18] An espoused aim of palliative care is to improve quality of life for dying people and those close to them.…”
Section: Introductionmentioning
confidence: 99%
“…whether artificial infusions would relieve thirst. A qualitative study among physicians found that they experienced fixed positive attitudes regarding the non‐provision of assisted hydration to terminally ill patients among hospice practitioners (Kingdon et al, 2022). ESPEN guideline (Druml et al, 2016) clearly state (Statement 20) that: ‘dryness of the mouth and thirst should first be counteracted by nursing measures such as lip care (cleaning and moistening the lips) and mouth care with mouthwash, as well as repeated provision of small amounts of fluids.…”
Section: Introductionmentioning
confidence: 99%